Short-term effects of complex training on agility with the ball, speed, efficiency of crossing and shooting in youth soccer players - Cavaco, B.; Sousa, N.; Machado dos Reis, V.; Garrido, N.; Saavedra, F.; Mendes, R.; Vilaca Alves, J. (Journal of Human Kinetics, 2014)
Complex training (CXT) is the result of a combination of strength and plyometric exercises in the same session. This method has recently been used in the preparation of athletes of different sports. The aim of the present study was to observe the acute effects of a CXT program of 6 weeks: i) on agility with the ball, sprinting and the efficiency of crossing and shooting in youth soccer players; ii) and the influence of the number of CXT sessions per week (one vs. two). Sixteen youth male soccer players were randomly divided into three groups: a group that performed one weekly CXT session (GCT1, n = 5, age: 13.80 ± 0.45 years); or a group that performed two weekly CXT sessions (GCT2, n = 5, age: 14.20 ± 0.45 years); or a control group that did not perform the CTX (n = 6, age: 14.20 ± 0.84 years). All groups maintained their regular soccer training sessions. No significant interactions were found between GCT1 and GCT2 in all variables. Significant statistical differences were identified (F = 1139, p = 0.02, µp2 = 0531) in the pre-test versus post-test, for both experimental groups, in shot effectiveness. In conclusion, the CXT program proved to be an effective method in boosting abilities and motor skills associated with soccer among young athletes, particularly in increasing shot effectiveness.